Stylistic peculiarities of the Dignity Revolution poetry - Горішна, Галина Михайлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the stylistic peculiarities of the Dignity Revolution poetry where special attention is paid to the fact that psychological perception of disastrous events in today’s reality determines stylistic features of Maidan poetry. It proves that emotional experience and chaotic expression of the historic, social, cultural events in Ukraine results in the language polyphony and apocalyptic syntax. Consequently, we can speak about special cultural and social shared world of Maidan poetry.